Estate Sector Women in the View of Public Theology: A Perspective Focussed on Thalawakella Region - Mary Winifreeda, S. (University of jaffna, 2024)
Public theology is an effort to make decisions for the common good from a Christian perspective. This study focuses on the challenges faced by the estate women from a public theological perspective. In the Sri Lankan economy, tea production plays a vital role, and women from the estate sector constitute a major part of the workforce. However, the problems faced by women working in tea estates have not yet been properly addressed. There are some articles on estate women; they focus on the common problems faced by them. The main objective of this study is to identify the challenges faced by the downtrodden women working in the tea estate, present their risk levels, and suggest solutions to their problems in the light of public theology. Therefore the hypothesis of this research is that the women working in tea estate sector have specific problems related to them. The primary data on women working in tea plantations has been collected through interviews, questionnaires and field visits. So observatory method has been used. The secondary data obtained from books, journals, articles, and statistical manuals has been used. This study focuses on the Talawakella region under the Nuwara Eliya Divisional Secretariat and it focuses on the women working at the St. Clair tea estate. Although both men and women from these families work in the tea plantations, their families continue to live in dire poverty. Also, lack of basic amenities is seen as impediments in engaging their work. When the status of these women who work in tea plantations is examined from a public theological view, their human dignity should be respected according to which the dignity of labour should be maintained, wages should be paid according to the work and justice should prevail. The problems faced by these women should not be confined to the family and neighborhood circle but appropriate solutions should be found. Additionally, this study could be useful for policymakers and women’s rights activists.
Keywords: Estate sector; Tea plantation; Public theology; Empowerment; Statistical